Beyond the Surface: Exploring the Relationship between Value Diversity and Team Creativity. Issue 2 (2nd April 2020) - Kirrane, Melrona; Kramer, Matthias; Lassleben, Hermann
ABSTRACT: Whether diversity enhances or impedes team creativity remains an issue of scholarly debate. Explanations of this ambiguity often lie in how diversity is both operationalized and measured. Eschewing the popular approach of using differences in objective criteria to signal diversity, a deep-level approach that focuses on differences in personal values is taken in this study. Value diversity is measured in the two forms of variety and separation and their associations with team creativity are explored. The investigation is augmented by considering the mediating role of team communication in these associations. The analysis was conducted on a sample of 98 teams, using both subjective and objective measures. The findings reveal that when considering value diversity in terms of variety, there is a positive association between diversity and team creativity. However, when the separation dimension of value diversity is considered, a negative association between diversity and team creativity is identified. Complex pathways pertaining to the role of communication within these relationships are also uncovered. In moving beyond rudimentary categories and measurement of diversity, this study further elucidates the complexity of the diversity–creativity relationship. Conclusions are drawn and implications for further research and managerial practice are derived.